Bioestratigrafía de la Formación Barranca Final, Neógeno de la Cuenca del Colorado, Argentina - Guler, Maria Veronica (2002)
Dinoflagellate cysts from the Barranca Final Formation type section are diverse and well preserved. The assemblages are dominated by the Order Gonyaulacales, with subordinate Peridiniales represented only by protoperidiniaceans. Based on selected dinoflagellate cyst events, and in accordance with the foraminiferal data, we suggest a Middle to Late Miocene age for the section. Piasecki ranges from latest Early Miocene or early Middle Miocene through Late Miocene has its range base within the Middle Miocene. The occurrences of these species together with the presence of (Wall) Reid confirms an age no older than Middle Miocene for the bottom of the section. The low representation of oceanic species, such as Nematosphaeropsis rigida 150% Wrenn (inner to outer? neritic), the diverse representation of protoperidinacean species (inner neritic), and the abundance of euryhaline forms, particularly specimens of the Operculodinium centrocarpum/israelianum Tuberculodinium vancampoae Lingulodinium hemicystum, reflect estuarine to inner neritic conditions for the lower part of the section palaeoenvironmental, the occurrence of oceanic to neritic markers coinciding with a glauconitic section, suggest a marine flooding surface.